ANALISIS BAURAN PEMASARAN (Marketing Mix) KERIPIK PISANG DI SENTRA INDUSTRI KERIPIK KOTA BANDAR LAMPUNG - Erinda Pradini; Dwi Haryono; Yaktiworo Indriani (Lampung University, 2021)
This study aims to analyze the marketing mix applied on the marketing activities and study the obstacles onapplying marketing mix, in addition to analyzing the marketing mix that should be carried out by banana agroindustry of “Askha Jaya Keripik Lampung”. This research was a case study conducted in January to February 2020 at the Bandar Lampung Industrial Chip Center in which data was analyzed by qualitative descriptive analysis method. The results of this study showed that the marketing mix carried out by Askha Jaya Agroindustry produced three types of banana chips, namely sliced, rounded and melted. The determination of the selling price was implemented by the cost plus pricing method. The distribution channels were conducted by two channels and promotions was carried out through personal selling, sales promotion, advertising and publicity. Some constraints faced by the agroindustry were the availability of products caused by the scarcity of raw materials, delaying in the process of services to consumers, product delivering time and imaging capture without permission on online marketing. The marketing mix that should be done was reducing the size of the product weight when there was scarcity of raw materials, adding price tags to the shop, and the need of sanctions for those who were not responsible for online marketing.Keywords: agroindustry, banana chips, marketing mix